Pemanfaatan mesin penggoreng otomatis pada proses produksi abon nabati kluwih Probolinggo - Maksin, Mastina; Haryono, Haryono; Puspitarini, Renny Candradewi; Basit, Abdul; Trismawati, Trismawati; Wiratomo, Giri Harto (IKIP SILIWANGI, 2025)
Kluwih vegetable floss is a local plant-based culinary innovation that is currently developing in Indonesia. As an alternative to meat floss, this product offers unique flavor, value, and nutritional content consisting of high carbohydrates, dietary fiber, and protein, as well as a very large and broad national market potential. Kluwih vegetable floss is a processed product in the form of fine fibers that resemble meat floss, but is made from plants found in the Pajarakan area of Probolinggo owned by the target partner. The purpose of this production is to provide a high-fiber and low-cholesterol food alternative that is very suitable for vegetarians and vegans. This potential is not wasted by the target partner to process kluwih fruit into kluwih vegetable floss with a very high selling value. Various problems arose in the production process caused by very limited resources and capital, such as in the production function of the frying process stage which still uses conventional tools (large pans). The existence of PKM grant assistance from the Directorate of Research and Community Service of the Ministry of Education and Culture in the manufacture of an automatic frying machine according to the target partner's needs was able to simplify the production process effectively and efficiently. By using this automatic frying machine, the Kluwih Vegetable Floss SME produces high-quality products packaged using a continuous band sealer. The automatic frying machine is able to cut down on time and reduce human resources so that employee energy can be diverted to other production functions at other stages and the frying stage no longer uses traditional tools. This automatic frying machine has undergone a trial process in Jember before being handed over to target partners in Probolinggo. The results of the field trial showed the effectiveness of the kluwih vegetable floss production process by properly regulating the temperature, machine pressure and machine maintenance procedures. The results obtained are that the machine produces very quickly, efficiently and produces very satisfactory results for target partners.